Canada : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
The spillovers from the U.S. economy to Canada have been assessed. It uses structural vector autoregressions to analyze the role of financial linkages in real and financial spillovers from the United States to Canada. The implications of Canada's predictable price level have been analyzed. Innovative small and medium-size enterprises have significantly greater difficulty in obtaining financing, reflecting reluctance by the banks to price risk. Canada has sufficiently flexible labor markets to absorb significant sectoral shocks without creating a high level of frictional unemployment.